1998
DOI: 10.1037/0735-7028.29.3.223
|View full text |Cite
|
Sign up to set email alerts
|

Military health care providers' views on prescribing privileges for psychologists.

Abstract: Selected military psychologists have been trained and privileged to independently prescribe psychotropic medications. lb explore the attitudes of health care professionals toward prescribing authority, a survey of 395 military psychiatrists, psychologists, primary care physicians, and social workers was conducted. Psychologists, physicians, and social workers supported prescribing privileges and continuation of the training program. Results suggested that support by physicians and social workers is based on im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In light of such considerations, many clinical psychologists maintain that the ability to prescribe psychotropic medications is crucial to their clients (Guiterrez & Silk, 1998) as well as for the profession to remain consistent with the ethical principles previously outlined. Such proponents contend that current prescription practices are not conducive to meeting the needs of their clients and thus fail to meet the ethical criteria for the profession (Klusman, 1998). By making it necessary for clients to see two mental-health-care professionals for treatment, time and economic concerns may prevent a great number of individuals that would benefit from psychotropic medications or the combination of these medications and psychotherapy, from obtaining them.…”
Section: Support For Prescriptive Authoritymentioning
confidence: 92%
See 1 more Smart Citation
“…In light of such considerations, many clinical psychologists maintain that the ability to prescribe psychotropic medications is crucial to their clients (Guiterrez & Silk, 1998) as well as for the profession to remain consistent with the ethical principles previously outlined. Such proponents contend that current prescription practices are not conducive to meeting the needs of their clients and thus fail to meet the ethical criteria for the profession (Klusman, 1998). By making it necessary for clients to see two mental-health-care professionals for treatment, time and economic concerns may prevent a great number of individuals that would benefit from psychotropic medications or the combination of these medications and psychotherapy, from obtaining them.…”
Section: Support For Prescriptive Authoritymentioning
confidence: 92%
“…Interestingly, these perspectives can be defined rather precisely along the lines of professional affiliation. Among the clinical psychologists surveyed in Ax, Forbes, and Thompson's study (1997), the vast majority were very supportive of the proposal to grant prescriptive authority to their field while the majority of individuals opposed to this measure are members of the medical profession, particularly in the field of psychiatry (Klusman, 1998). Each perspective has been shown to present arguments that use ethical concerns as an integral part of the logic driving it.…”
mentioning
confidence: 95%
“…Some of the program's psychiatrists, physicians, and graduates expressed doubts about the safety and effectiveness of psychologists prescribing independently outside of the interdisciplinary team of the military context. This latter concern has been echoed in a survey of military psychiatrists, nonpsychiatric physicians, and social workers (Klusman, 1998). Given the likelihood that other programs would lack some of the advantages of the PDP, and would provide less training than some of the PDP graduates received, we question how well the conditions of the PDP would be duplicated.…”
Section: Projectmentioning
confidence: 99%
“…The other third were unsure or opposed. More recent surveys continue to suggest inconsistent attitudes among psychologists (Klusman, 1998; Pimental, Stout, Hoover, & Kamen, 1997; Piotrowski & Keller, 1996). One survey indicated less support among older psychologists and women (Massoth, McGrath, Bianchi, & Singer, 1990), while another found no significant correlation between support for the prescription privileges and either age or gender (Ferguson, 1997).…”
Section: Attitudes About Psychologists' Prescriptive Authoritymentioning
confidence: 99%
“…Although momentum is building for prescriptive authority at the state level, little progress has been made toward prescriptive authority for psychologists in the military since the end of the PDP. In a survey of military health care providers, Klusman (1998) found that a majority of active duty psychologists, primary care physicians, and social workers (though not psychiatrists) from the U.S. Army, Navy, and Air Force favored extending prescriptive authority to appropriately trained psychologists, primarily for the purpose of increasing access to care. Although the study did not deal directly with operational environments, it is reasonable to assume that this logic would extend to combat zones.…”
mentioning
confidence: 99%